The THE EFFECT OF INVESTOR SENTIMENT ON COMPANY CAPITAL STRUCTURE: AN EMPIRICAL APPROACH IN THE FINANCIAL INDUSTRY - Alawiyah, Diana Astutik; Mulyati, Sri (Komunitas Manajemen Kompetitif, 2025)
This study aims to empirically analyze the influence of investor sentiment on the capital structure of companies in the financial industry and examine the role of firm size as a moderating variable. Using a quantitative approach with panel data from 96 financial sector companies listed on the Indonesian Stock Exchange (IDX) during the 2021-2024 period, this study analyzes 384 data observations. Capital structure is measured by the Debt to Equity Ratio (DER), investor sentiment is proxied by Trading Volume Activity (TVA), and firm size is measured by the Natural Logarithm of Total Assets. The study’s findings indicate that investor sentiment significantly and positively influences a company’s capital structure. In other words, when market sentiment is strong, companies often increase their debt levels. Furthermore, firm size is shown to play a significant moderating role in this relationship, but in a negative direction. This means that the influence of investor sentiment on a company’s capital structure weakens in large companies. These findings, highlight the importance of investor sentiment in financing decisions, especially for small companies that are more vulnerable to market fluctuations, and provide implications for financial managers and regulators in formulating strategies and policies.